1995
DOI: 10.1021/bi00018a028
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding Specificity of the EcoRV Restriction Endonuclease Is Increased by Mg2+ Binding to a Metal Ion Binding Site Distinct from the Catalytic Center of the Enzyme

Abstract: In contrast to many other type II restriction endonucleases, EcoRV binds specifically to DNA only in the presence Mg2+. According to the co-crystal structure of an EcoRV-DNA complex, Mg2+ ion(s) bind to the active site of EcoRV liganded by Glu45, Asp74, and Asp90. Here we present experimental evidence suggesting that the EcoRV-DNA complex also interacts with Mg2+ ions at other sites: (i) We have prepared an EcoRV triple mutant, in which all acidic amino acids in the catalytic center are replaced by alanine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 22 publications
5
56
1
Order By: Relevance
“…It also cannot be ruled out that the lower Mg(II) binding stoichiometries observed for the Glu-9 and Glu-115 mutants might be due to the effect of the mutations on the protein structure and not due to loss of a Mg(II) coordination site. A Mg(II) binding site distinct from the catalytic center has been proposed for the EcoRV restriction endonuclease (32). E. coli DNA topoisomerase I may also have a second Mg(II) binding site away from the active site region that is required for relaxation activity because of its effect on the protein conformational changes that take place during the relaxation reaction cycle (28).…”
Section: Discussionmentioning
confidence: 99%
“…It also cannot be ruled out that the lower Mg(II) binding stoichiometries observed for the Glu-9 and Glu-115 mutants might be due to the effect of the mutations on the protein structure and not due to loss of a Mg(II) coordination site. A Mg(II) binding site distinct from the catalytic center has been proposed for the EcoRV restriction endonuclease (32). E. coli DNA topoisomerase I may also have a second Mg(II) binding site away from the active site region that is required for relaxation activity because of its effect on the protein conformational changes that take place during the relaxation reaction cycle (28).…”
Section: Discussionmentioning
confidence: 99%
“…M13 DNA, containing R p -phosphorothioates, showed that GATsATC sequences were very refractory to hydrolysis and substitution elsewhere tended to reduce cutting rates (32). Very recently, the phosphorothioate oligonucleotides used in this study have been used to show the presence of a metal ion binding site distinct from the catalytic center (55). In this publication, we examine the effects of both isomers of phosphorothioates within and immediately flanking the EcoRV restriction site on endonuclease-catalyzed hydrolysis and relate the results found to the available crystal structures.…”
mentioning
confidence: 88%
“…Two further points deserve mentioning. First, by comparing the Mg 2ϩ -and Mn 2ϩ -catalyzed cleavage of the phosphorothioates, an additional metal ion, remote from the active site, was proposed to bind to the GACGpATATCGTC phosphate (55). The exact role of this metal ion in selectivity remains obscure, but it could certainly be incorporated as an additional structural element in the network illustrated.…”
Section: Figmentioning
confidence: 99%
“…1a), a 20-mer oligonucleotide substrate was chosen for a detailed kinetic analysis of the mutant proteins under steadystate conditions. This substrate can be expected to mimic a high molecular weight DNA as it is longer than the entire binding pocket of EcoRV, which covers 14 -16 bp (5,20). By variation of the substrate concentration over 5 orders of magnitude, it was possible to determine the kinetic parameters K m and k cat for all mutants except the T37A mutant (Table III).…”
Section: Selection Generation and Purification Of Ecorv Mutants-mentioning
confidence: 99%